Function and mechanism of cohesin REC8 during meiosis - DAI Jingling; YU Chao (浙江大学学报. 农业与生命科学版, 2023)
Cohesin is a functionally and evolutionarily conserved multi-subunit protein complex that is required for sister chromatid cohesion and chromatin loop structure in both mitosis and meiosis. The meiotic cell-cycle consisting of one DNA replication and two successive rounds of chromosome segregation completes the segregation of homologous chromosomes and sister chromatids. Cohesin is crucial for faithful and proper segregations. There is a group of distinctive cohesin subunits that are only expressed in meiotic cells. The study of meiosis-specific cohesin is of great significance for understanding chromosome architecture and dynamics in meiosis. REC8 is a typical meiosis-specific cohesin subunit that plays essential roles in sister chromatid cohesion and meiotic chromosome events. Here, we review the function and mechanism of meiotic cohesin REC8 based on the current study and hypothesize that phosphorylation modification and microRNAs (miRNAs) could be the subsequent research directions of REC8.